Pengaruh Pemberian Ekstrak Daun Beluntas (Pluchea indica L) terhadap Total Kolesterol Darah Broiler - Yana Sukaryana; Y. Priabudiman (Politeknik Negeri Lampung., 2014)
The purpose of study was to determine the potential leaf extract Pluchea indica L at broiler in lowering cholesterol, as well as the exact time of administration so that the plant can be used as an alternative to veterinary medicinal plants without any negative effect on productivity. The experimental design used was a complete randomized design (CRD) consisting of 4 treatments with 6 replicates, each occupied by 4 broilers. P1 treatment was leaf extract Pluchea indica L for 3 weeks starting at the age of 1 week, P2 treatment was leaf extract Pluchea indica L for 2 weeks starting at the age of 2 week, P3 treatment was leaf extract Pluchea indica L for 1 weeks starting at the age of 3 week, and P4 treatment without leaf extract Pluchea indica L for maintenance. Examination of the blood cholesterol level was done through a blood sample from the brachial vein any chickens taken at random to represent each repeat unit during 35 day old chicks. Experimental data processed by analysis of variance and if there is a treatment effect followed by Duncan's multiple range test. The results showed that there are significant leaf extract Pluchea indica L to total cholesterol, HDL, and LDL blood broiler. P1 treatment is beluntas leaf extract for 3 weeks starting at the age of 1 week produced a total content of cholesterol (156 mg / dl), HDL (44 mg / dl), and LDL (144 mg / dl) of blood lowest broiler. Keywords : Pluchea indica L, blood cholesterol, broiler.